Method for preparing sodium ion hard carbon negative electrode material by depolymerizing and separating lignin and application of sodium ion hard carbon negative electrode material

Through membrane separation technology, lignin is processed in a graded manner and carbonized manner, and lignin hard carbon negative electrode material suitable for sodium ion batteries is prepared, which solves the problem of lignin-based hard carbon in sodium storage, cycle stability and fast charging performance. Challenge, achieving more efficient and even material properties.

CN119390046AActive Publication Date: 2025-02-07INST OF CHEM IND OF FOREST PROD CHINESE ACAD OF FORESTRY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411359750.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2025-02-07
Estimated Expiration
2044-09-27

AI Technical Summary

Technical Problem

In the prior art, lignin-based hard carbon has challenges such as economicality and first-time Coulomb efficiency in terms of sodium storage, circulation stability and fast charging performance, and its molecular structure is complex, resulting in uneven performance.

Method used

After oxidation and depolymerization of lignin, membrane separation technology is used to grade lignin in the molecular weight range, and pre-carbonization and high-temperature carbonization are performed to prepare lignin hard carbon of different molecular weight ranges for the preparation of sodium ion hard carbon anode material.

Benefits of technology

The structural directional regulation of lignin hard carbon is achieved, the sodium storage capacity, cycle stability and fast charging performance in sodium ion batteries are improved, and the production cost is reduced, and the uniformity and processability of materials are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390046A_ABST
    Figure CN119390046A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a sodium ion hard carbon negative electrode material through lignin depolymerization and separation and application, and belongs to the technical field of lignin depolymerization and separation and sodium ion hard carbon negative electrode material production. The method comprises the following steps: oxidizing and depolymerizing lignin into small molecules, performing fractional separation through a membrane separation instrument to obtain lignin with fractional molecular weight ranges of more than 3K Da, 3K-2K Da, 2K-1K Da, 1K-500Da, 500-200Da and less than 200Da, and performing pre-carbonization and high-temperature carbonization treatment to prepare the lignin-based hard carbon. In the carbonization and high-temperature reforming process of lignin with different molecular weight segments, due to different exposure degrees of molecular structures, cross-linked structures and active sites of the lignin, directional regulation and control of a lignin-based hard carbon microcrystalline structure are realized; the problems of poor energy storage performance, indefinite sodium storage mechanism and the like of lignin-based hard carbon caused by non-uniform molecular structure and unknown structure of the precursor are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lignin depolymerization and separation and sodium ion negative electrode hard carbon material production, and specifically relates to a method and application of lignin depolymerization and separation for preparing sodium ion hard carbon negative electrode material. Background Art

[0002] As a negative electrode material, hard carbon has received widespread attention for its application in sodium-ion batteries. Its unique long-range ordered and short-range disordered carbon microcrystalline structure makes it the preferred negative electrode material for sodium-ion batteries. Hard carbon has the advantages of high capacity, fast charging support, and strong safety. These characteristics enable it to meet the needs of high energy density for mobile power and home appliance energy storage applications. Although the diversity and complexity of the precursor structure have led to controversy over the specific mechanism of sodium storage in hard carbon materials. In addition, in practical applications, there are relatively few research reports on sodium-ion batteries that can support large current fast charging and maintain good cycle stability, but the application prospects of hard carbon have been recognized.

[0003] Lignin is mostly industrial waste produced by paper mills and cellulosic ethanol plants. If it can be used as a sustainable precursor for hard carbon, it will greatly benefit environmental protection and sustainable development. Lignin-based hard carbon has a rich closed pore structure and an external pore structure with different pore sizes. These structural characteristics are conducive to the storage of sodium ions, thereby providing a higher sodium storage capacity. On the one hand, the internal crystal arrangement of lignin-based hard carbon is disordered and the interlayer spacing is large, which makes the expansion and contraction of the hard carbon negative electrode more uniform during the discharge process, increases its cycle stability, charge and discharge performance, and prolongs the cycle life of the sodium ion battery; on the other hand, the volume of lignin-based hard carbon becomes smaller after sodium insertion, and has good low temperature and fast charging performance. These characteristics make it the preferred negative electrode material for sodium ion batteries. Lignin-based hard carbon has the advantages of high sodium storage capacity, excellent cycle stability, good sodium insertion performance and sustainability in sodium storage, but there are also challenges in terms of economy and first coulombic efficiency. Therefore, through proper treatment and improvement, lignin-based hard carbon is expected to become one of the preferred negative electrode materials for sodium ion batteries.

[0004] The advantages of lignin with uniform molecular weight are mainly reflected in improving the application value and stability of lignin, as well as optimizing its chemical and physical properties. Through classification, the heterogeneity of lignin, including the polydispersity of molecular weight and the complexity of structure, can be reduced, thereby improving its performance stability in downstream applications. The polydispersity of lignin molecular weight leads to its non-uniform structure and performance, causing unstable product performance and reducing the application value of the product. The use of classification methods to classify lignin with similar reaction activity and application performance based on molecular weight is an effective means to solve the above problems. In this way, lignin with different molecular weight ranges can be obtained, and the lignin structure and product performance can be obtained by comparing and analyzing different lignin classification methods. According to the characteristics and performance of lignin at each level, it can be used in a targeted manner, providing guidance for the classification of lignin and subsequent product development under different extraction methods and product performance requirements, and promoting the stabilization and high value development of lignin products. In addition, graded lignin also helps to improve the uniformity of lignin and improve the reactivity of its unique groups, further broadening the application of lignin in materials science, chemical production and other fields. These advantages further improve its application value and optimize its chemical and physical properties, making fractionated lignin a hot topic in research and industrial applications. Summary of the invention

[0005] The technical problem solved by the present invention is to provide a method for preparing sodium ion hard carbon negative electrode material by depolymerization and separation of lignin; another technical problem to be solved by the present invention is to provide a sodium ion hard carbon negative electrode material prepared by depolymerization and separation of lignin prepared by the above method; another technical problem to be solved by the present invention is to provide an application of lignin depolymerization and separation in preparing sodium ion hard carbon negative electrode material.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing sodium ion hard carbon negative electrode material by depolymerization and separation of lignin, after oxidative depolymerization of lignin, membrane separation is used to obtain lignin with graded molecular weight ranges of more than 3K Da, 3K-2K Da, 2K-1K Da, 1K-500Da, 500-200Da, and less than 200Da, and the lignin in each molecular weight range is respectively subjected to pre-carbonization and high-temperature carbonization treatment to prepare corresponding lignin hard carbon for preparing sodium ion hard carbon negative electrode material.

[0008] The preparation process of the depolymerized lignin is as follows: dispersing the lignin into deionized water, adding H2O2 and a composite alkali, and depolymerizing to prepare a depolymerized lignin solution.

[0009] The type of the lignin is selected from any one of sulfate lignin, sulfonate lignin, alkali lignin and hydrolyzed lignin, the initial lignin molecular weight is 6K-8K Da, and the purity is ≥93%.

[0010] The method for precipitating the lignins with different molecular weights from the retained liquid is rotary evaporation at a temperature of 50-80°C.

[0011] The method for preparing sodium ion hard carbon negative electrode material by depolymerization and separation of lignin has the following specific steps:

[0012] (1) dispersing lignin in deionized water, adding H2O2 and a composite alkali, depolymerizing, and obtaining a depolymerized lignin solution;

[0013] (2) using a membrane separation instrument to separate the depolymerized lignin obtained in step (1) according to the molecular weight cutoff size, drying and weighing the lignin in different molecular weight ranges, crushing, ball milling and sieving to obtain a small molecular weight lignin powder;

[0014] (3) The small molecular weight lignin powder obtained in step (2) is carbonized, washed with HCl aqueous solution and distilled water until neutral and dry, and placed in a tubular furnace in an argon atmosphere for high-temperature structural reforming to obtain lignin-based hard carbon.

[0015] In the step (2), the carbonization temperature is 600-800° C., and the carbonization apparatus is a muffle furnace without any atmosphere and a tubular furnace with argon atmosphere.

[0016] The high temperature reforming temperature of step (3) is 1200-1600°C.

[0017] The method for preparing sodium ion hard carbon negative electrode material by depolymerizing and separating lignin can prepare small molecule lignin-based hard carbon.

[0018] The application of the depolymerized and separated lignin-based hard carbon in the negative electrode material of sodium ion batteries.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] (1) The present invention utilizes a lignin membrane separator to grade and separate depolymerized lignin through ceramic membranes and organic membranes with different molecular weight cutoffs, regulates the molecular weight of lignin, its distribution range and reactive functional groups, and achieves directional regulation of lignin and its structure during carbonization. This solves the problems of complex molecular structure of lignin that is difficult to analyze, few reactive sites, low carbon yield of hard carbon, and poor carbon storage performance of untreated lignin after pyrolysis.

[0021] (2) The present invention uses graded lignin as raw material to prepare hard carbon. Compared with traditional macromolecular lignin raw materials, the lignin separated by the present invention has a small molecular weight and a smaller and smaller distributed PDI, which means that the molecular weight distribution of lignin is more uniform, which helps to improve the processability of the material.

[0022] (3) The modified lignin hard carbon structure of the present invention is more uniform and has a smaller molecular weight, and a carbon microcrystalline structure with a higher degree of disorder can be obtained, which is more conducive to improving the electrochemical performance of the negative electrode material of the sodium ion battery.

[0023] (4) The method of the present invention is simple to operate and has low energy consumption, and is also of reference value for preparing biomass-based hard carbon from other types of graded lignin. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The GPC molar mass distribution diagrams of the undepolymerized lignin in Comparative Example 1 and the depolymerized and separated lignin in Examples 1-4, above 3K, 3K-1K, 1K-500, and below 500. DETAILED DESCRIPTION

[0025] The present invention is further illustrated below in conjunction with specific examples. The examples are implemented based on the technical solutions of the present invention. It should be understood that these examples are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0026] In the present application, lignin above 3K Da is referred to as 3K or more; lignin of 3K-1K Da is referred to as 3K-1K; lignin of 1K-500 Da is referred to as 1K-500; and lignin below 500 Da is referred to as 500 or less.

[0027] The test methods used in this application are as follows:

[0028] 1. Molecular structure property test

[0029] The molecular weight of the sample was tested by Agilent 1260 (GPC): the detector was Agilent RID G1362A; the chromatographic column was Waters Ultrahydrogel, 300×7.8mm, 500-250-120A; the mobile phase was 0.1mol / L NaNO3 aqueous solution; the flow rate was 1mL / min; the temperature was 40°C; the standard was PEG; and the solvent was water.

[0030] 2. Battery performance test (discharge specific capacity (mAh g -1 ) and first effect)

[0031] 2.1 Battery Production

[0032] Preparation of the electrode: The hard carbon material, the conductive agent (super-P) and the binder (PVDF) were mixed in a mass ratio of 7:1:1, and NMP was used as a dispersant to prepare a slurry, which was coated on a copper foil and dried in a blast drying oven at 80°C for 12 hours. The dried electrode sheet was punched into a circular electrode sheet with a diameter of 15 mm for later use.

[0033] Assembly of button half-cell: The battery is assembled in an argon glove box with moisture and oxygen content less than 0.01ppm respectively, using the battery shell specified in CR2032, and the electrolyte is 1mol / L NaPF6 (the solvent is a mixture of ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate with a volume ratio of 1:1:1). The metal sodium sheet is used as both the counter electrode and the reference electrode, and the diaphragm is a GF / D glass fiber diaphragm. The battery is assembled in the order of positive electrode shell, electrode sheet, diaphragm, sodium sheet, gasket, shrapnel and negative electrode shell from bottom to top.

[0034] 2.2 Performance Testing

[0035] The constant current charge and discharge test (GCD) was performed on the CT-6008Tn battery testing system.

[0036] Example 1

[0037] (1) Preparation of depolymerized lignin

[0038] 20 g of sodium lignin sulfonate was dispersed in 20 mL of deionized water, and then 8 g of 30 wt% H2O2 and 10 g of composite alkali (sodium hydroxide: ammonia water = 1:1, mass ratio) were added, followed by depolymerization at 40°C for 0.5 h to obtain a depolymerized lignin solution.

[0039] (2) Fractionation of depolymerized lignin

[0040] The obtained depolymerized lignin solution was diluted and added into a membrane separation instrument. Two types of lignin, one above 3K Da and one below 3K Da, were obtained through a ceramic membrane with a retention capacity of 3K Da. The lignin above 3K Da was dried after rotary evaporation at 60°C to obtain a sample.

[0041] (3) Preparation of lignin-based hard carbon

[0042] First, a certain amount of lignin powder with a temperature of more than 3K Da was weighed and carbonized (600℃ for 2h in a muffle furnace). Then, it was washed by boiling with a 1mol / L HCl aqueous solution and then washed with distilled water until neutral and dry. Finally, it was placed in a tubular furnace with an argon atmosphere for high-temperature structural reforming at 1300℃ to obtain lignin-based hard carbon.

[0043] Example 2

[0044] (1) Preparation of depolymerized lignin: the same as step (1) of Example 1.

[0045] (2) Fractionation of depolymerized lignin

[0046] The obtained depolymerized lignin solution was diluted and added into a membrane separation instrument. Two types of lignin, 3K-1K Da and below 1K Da, were obtained through a ceramic membrane with a retention capacity of 1K Da. The lignin in the range of 3K-1K Da was rotary evaporated at 60°C and then dried to obtain a sample.

[0047] (3) Preparation of lignin-based hard carbon

[0048] First, a certain amount of 3K-1K Da lignin powder was weighed and carbonized (600℃2h, muffle furnace), then boiled and washed with 1mol / L HCl aqueous solution, and then washed with distilled water until neutral and dry; finally, it was placed in a tubular furnace with argon atmosphere for high-temperature structural reforming at 1300℃ to obtain lignin-based hard carbon.

[0049] Example 3

[0050] (1) Preparation of depolymerized lignin: the same as step (1) of Example 1.

[0051] (2) Fractionation of depolymerized lignin

[0052] The obtained depolymerized lignin solution was diluted and added into a membrane separation instrument. Two types of lignin, 1K-500Da and below 500Da, were obtained through a ceramic membrane with a retention capacity of 500Da. The lignin in the range of 1K-500Da and below 500Da was rotary evaporated at 60°C and then dried to obtain a sample.

[0053] (3) Preparation of lignin-based hard carbon

[0054] First, a certain amount of 1K-500Da and lignin powder below 500Da was weighed and carbonized (600℃2h, muffle furnace), then boiled and washed with 1mol / L HCl aqueous solution, and then washed with distilled water until neutral and dry; finally, it was placed in a tubular furnace with argon atmosphere for high-temperature structural reforming at 1300℃ to obtain lignin-based hard carbon.

[0055] Comparative Example 1

[0056] Commercially purchased undepolymerized sodium lignin sulfonate powder was carbonized at 600°C, washed with HCl aqueous solution and distilled water until neutral and dry, and placed in a tubular furnace in an argon atmosphere for high-temperature structural reforming at 1300°C to obtain lignin-based hard carbon.

[0057] The molecular structure properties and battery performance of the samples prepared in the above Examples 1-3 and Comparative Example 1 were tested. The test results are shown in Table 1, and the optimal range of the molecular weight of lignin is 3K-1K.

[0058] Table 1 Sodium storage properties of lignin-based hard carbons in different molecular weight ranges

[0059]

[0060] Example 4

[0061] (1) Preparation of depolymerized lignin

[0062] 20 g of alkali lignin was dispersed in 20 mL of deionized water, and then 8 g of 30 wt% H2O2 and 10 g of composite alkali (sodium hydroxide: ammonia water = 1:1, mass ratio) were added, followed by depolymerization at 40°C for 0.5 h to obtain a depolymerized lignin solution.

[0063] (2) Fractionation of depolymerized lignin

[0064] The obtained depolymerized lignin solution was diluted and added into a membrane separation instrument. Two types of lignin, one above 3K Da and one below 3K Da, were obtained through a ceramic membrane with a retention capacity of 3K Da. The lignin above 3K Da was rotary evaporated at 60°C and then dried to obtain a sample.

[0065] (3) Preparation of lignin-based hard carbon

[0066] First, a certain amount of lignin powder with a temperature of more than 3K Da was weighed and carbonized (600℃ for 2h in a muffle furnace), then washed by boiling with a 1mol / L HCl aqueous solution, and then washed with distilled water until neutral and dry; finally, it was placed in a tubular furnace in an argon atmosphere for high-temperature structural reforming at 1300℃ to obtain lignin hard carbon.

[0067] Example 5

[0068] (1) Preparation of depolymerized lignin: the same as step (1) of Example 1.

[0069] (2) Fractionation of depolymerized lignin

[0070] The obtained depolymerized lignin solution was diluted and added into a membrane separation instrument. Two types of lignin, one above 3K Da and one below 3K Da, were obtained through a ceramic membrane with a retention capacity of 3K Da. The lignin above 3K Da was dried after rotary evaporation at 60°C to obtain a sample.

[0071] (3) Preparation of lignin-based hard carbon

[0072] First, a certain amount of lignin powder with a diameter of more than 3K Da was weighed and carbonized (600℃ for 2h in a tubular furnace under an argon atmosphere), then boiled and washed with a 1mol / L HCl aqueous solution, and then washed with distilled water until neutral and dry; finally, it was placed in a tubular furnace under an argon atmosphere for high-temperature structural reforming at 1300℃ to obtain lignin-based hard carbon.

[0073] Example 6

[0074] (1) Preparation of depolymerized lignin: the same as step (1) of Example 1.

[0075] (2) Fractionation of depolymerized lignin

[0076] The obtained depolymerized lignin solution was diluted and added into a membrane separation instrument. Two types of lignin, one above 3K Da and one below 3K Da, were obtained through a ceramic membrane with a retention capacity of 3K Da. The lignin above 3K Da was dried after rotary evaporation at 60°C to obtain a sample.

[0077] (3) Preparation of lignin-based hard carbon

[0078] First, a certain amount of lignin powder above 3K Da was weighed and carbonized (600℃2h, muffle furnace), then boiled and washed with 1mol / L HCl aqueous solution, and then washed with distilled water until neutral and dry; finally, it was placed in a tubular furnace with argon atmosphere for high-temperature structural reforming at 1400℃ to obtain lignin-based hard carbon.

[0079] The molecular structure properties and battery performance of the samples prepared in Examples 2, 5-6 and Comparative Example 1 were tested, and the test results are shown in Table 2. The effects of the selection of small molecular lignin and lignin types in the carbonization process of hard carbon, the pre-carbonization atmosphere, and the high-temperature reforming temperature on the sodium storage performance of hard carbon are mainly explained.

[0080] Table 2 Sodium storage performance of lignin-based hard carbon under different lignin types, carbonization atmospheres, and high-temperature reforming temperature conditions

[0081]

[0082] The conditions screened in Table 2 are mainly the reaction conditions involved in the entire reaction process. The type of lignin and the high-temperature reforming temperature have no significant effect on the performance of the prepared lignin-based hard carbon. However, the reversible capacity and first efficiency of the lignin-based hard carbon obtained by isolating oxygen during the pre-carbonization process and then refining at 1300°C are improved.

[0083] The molecular weight distribution of the samples prepared in the above comparative examples and embodiments is shown in Table 3.

[0084] Table 3 GPC data of lignin in different molecular weight ranges after depolymerization and separation

[0085]

[0086] The smaller the molecular weight distribution PDI (polydispersity index) is, the more uniform the molecular weight distribution of the polymer is. As shown in Table 3, the molecular weight of the original lignin (undepolymerized) (1656, 3733 g.mol -1) is the largest, mainly because the molecular weight of lignin itself is very large and has multiple molecular weight ranges, and its molecular weight distribution coefficient PDI is also the largest at 2.25, indicating that its molecular weight distribution is the most uneven. Figure 1 It can be clearly seen from the molecular weight distribution diagram that the molecular weight and PDI of lignin after fractionation are getting narrower and narrower. The molecular weight distribution of lignin below 500Da is the narrowest, that is, the molecular weights of the molecules in the mixture are relatively close and the distribution is the most uniform. However, the hard carbon sodium storage performance prepared from the lignin below 500 with the narrowest molecular weight is not the best. The main reason is that there are no partial oxygen-containing functional groups on the above-mentioned lignin that are conducive to the construction of hard carbon microcrystalline structure. In addition to the lignin below 500, the distribution of 1K-500 lignin is also relatively uniform, but its molecular weight distribution is very similar to the lignin data in the range of 3K-1K, but the latter has more active functional groups, which is conducive to the subsequent carbonization and improvement of sodium storage performance. Compared with undepolymerized lignin, the sodium storage performance of lignin that has been gradually approached to homogenization by low molecular weight after depolymerization and regulation of molecular weight distribution has been greatly improved. This can prove that the molecular weight distribution PDI is getting smaller and smaller, which means that the molecular weight distribution of lignin is more uniform, which will help to improve the physical properties and processing properties of the material, thereby optimizing product quality and production efficiency (Comparative Example 1, Examples 1-3). After comparing the sodium storage performance of lignin-based hard carbon regulated by different lignin types, carbonization atmospheres, high-temperature reforming temperatures and other conditions, it can be established that lignin with a molecular weight range of 3K-1K and a PDI of 1.20 is the best hard carbon precursor in this experimental system, and the best regulation scheme for lignin-based hard carbon is Example 2.

[0087] The sodium storage performance of the undepolymerized lignin of comparative example 1 and the lignin-based hard carbons of different molecular weight ranges obtained in Examples 1-6 were tested. The results in Table 1 show that with the deepening of the lignin fractionation, the molecular weight of lignin gradually decreases, and the sodium storage performance of the obtained lignin-based hard carbons shows great differences. Among these lignin-based hard carbon materials, the lignin-based hard carbons prepared by fractionating the lignin with a molecular weight range of 3K-1K have a sodium storage performance of 0.05A g -1 The highest reversible capacity is 358.07 mAh g -1 , the initial Coulombic efficiency is 76%.

[0088] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing sodium ion hard carbon negative electrode material by depolymerization and separation of lignin, characterized in that: After oxidative depolymerization of lignin, membrane separation is used to obtain lignin with graded molecular weight ranges of above 3K Da, 3K-2K Da, 2K-1K Da, 1K-500Da, 500-200Da, and below 200Da. The lignin in each molecular weight range is pre-carbonized and high-temperature carbonized to prepare the corresponding lignin hard carbon, which is used to prepare sodium ion hard carbon negative electrode materials.

2. The method for preparing sodium ion hard carbon negative electrode material by depolymerization and separation of lignin according to claim 1, characterized in that: The preparation process of the depolymerized lignin is as follows: dispersing the lignin into deionized water, adding H2O2 and a composite alkali, and depolymerizing to prepare a depolymerized lignin solution.

3. The method for preparing sodium ion hard carbon negative electrode material by depolymerization and separation of lignin according to claim 2, characterized in that: The type of the lignin is selected from any one of sulfate lignin, sulfonate lignin, alkali lignin and hydrolyzed lignin, the initial lignin molecular weight is 6K-8K Da, and the purity is ≥93%.

4. The method for preparing sodium ion hard carbon negative electrode material by depolymerization and separation of lignin according to claim 1, characterized in that: The method for precipitating the lignins with different molecular weights from the retained liquid is rotary evaporation at a temperature of 50-80°C.

5. The method for preparing sodium ion hard carbon negative electrode material by depolymerization and separation of lignin according to claims 1-2, characterized in that: The specific steps are as follows: (1) dispersing lignin in deionized water, adding H2O2 and a composite alkali, depolymerizing, and obtaining a depolymerized lignin solution; (2) separating the depolymerized lignin solution obtained in step (1) by using a membrane separation instrument according to the molecular weight cutoff size grade, drying and weighing the lignin in different molecular weight ranges, and obtaining a small molecular weight lignin powder after crushing, ball milling and sieving; (3) The small molecular weight lignin powder obtained in step (2) is carbonized, washed with HCl aqueous solution and distilled water until neutral and dry, and placed in a tubular furnace in an argon atmosphere for high-temperature structural reforming to obtain lignin-based hard carbon.

6. The method for preparing sodium ion hard carbon negative electrode material by depolymerization and separation of lignin according to claim 5, characterized in that: In the step (2), the carbonization temperature is 600-800° C., and the carbonization apparatus is a muffle furnace without any atmosphere and a tubular furnace with argon atmosphere.

7. The method for preparing sodium ion hard carbon negative electrode material by depolymerization and separation of lignin according to claim 5, characterized in that: The high temperature reforming temperature of step (3) is 1200-1600°C.

8. According to the method for preparing sodium ion hard carbon negative electrode material by depolymerization and separation of lignin as described in claim 5, small molecule lignin-based hard carbon is prepared.

9. Use of the depolymerized and separated lignin-based hard carbon according to claim 8 in negative electrode materials for sodium ion batteries.

Citation Information

Patent Citations

  • Method for preparing electrode materials for different carbon-based supercapacitors by regulating molecular weight of xylogen

    CN109659151A

  • High-performance biomass derived hard carbon negative electrode material as well as preparation method and application thereof

    CN117049509A

  • Molecular-weight-controllable oxidized lignin modified phenolic resin-based hard carbon as well as preparation method and application thereof

    CN117963877A